T-plate fixation for unstable proximal clavicula fractures - Yi Zheng; Xin-Hua Yuan; Yi-Hong Yin; Wei-Bin Wang; Qing-Song Fu; Qing-Jiang Pang (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the clinical results of T-plate fixation and anterior sternoclavicular ligament repair in proximal clavicle fractures. Methods: Between August 2013 and August 2016, a total 12 patients (10 men and 2 women; mean age: 44.1 ± 9.1 years (range, 25–59 years)) with unstable proximal clavicle fractures (Throckmorton, type D) were treated with T-type plate fixation, bridging the sternoclavicular joint, and anterior sternoclavicular ligament repair. Average operative time, associated injuries, postoperative complications, postoperative fracture healing time and follow-up time were recorded. The outcomes were evaluated with radiographic assessment, visual analog scale (VAS) pain score and Rockwood SCJ scoring system. All the patients were evaluated on postoperative 3rd, 6th, and 12th months. Results: The average surgery time was 78.0 ± 8.47 minutes while fracture healing time was 4.51 ± 0.95 months. According to Rockwood SCJ scoring system, 9 cases (75%) were in excellent, 2 cases (16.7%) in good and 1 case (8.3%) in fair condition at 12 months follow-up. The average Rockwood SCJ score was 7.7 ± 0.75 preoperatively, 12.7 ± 0.86 by 3 months, 13.0 ± 0.73 by 6 months and 13.3 ± 0.49 by 12 months. The VAS pain score was 7.9 ± 1.15 (preoperative score), 3.4 ± 1.52 (3 months follow-up), 3.0 ± 1.32 (6 months follow-up) and 2.1 ± 1.07 (12 months follow-up). The VAS and Rockwood SCJ scores were significantly improved postoperatively (p < 0.05). There was no intraoperative complication, while one patient had redislocation of the sternoclavicular joint after implant removal. Conclusion: T-type plate fixation with anterior sternoclavicular ligament repair might be a reliable and effective treatment method in unstable proximal clavicle fractures (type D) with few complications and satisfactory clinical results after 12 months follow-up. Level of evidence: Level IV, therapeutic study. Keywords: Clavicula fracture, Proximal, Sternoclavicular ligament, Plate, Internal fixation